Situation Report: Poland, 19 March 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Glemp and Jaruzelski Talk about the Pope's Visit The Taming of Intellectual Dissent: The Fine Arts / by Ewa Chciuk Celt Sejm Examines the Three-Year Economic Plan A Profile of Anna Walentynowicz / by Anna Swidlicka Sundry Items